THE MAGNETIC FIELD REVERSAL AS A COROLLARY TO A MECHANISM OF THE ORIGIN OF SAN LUIS POTOSIIRAL STRUCTURE - PISMIS, P (UNAM, Instituto de Astronomía, CD MEXICO, DF, MEX, 1965)
A brief review is given of a theory advanced previously by the author to account for the origin and development of spiral arms in a galaxy. It is shown that a corollary of the theory may explain (a) The position of the spiral arms alternately up and down
BOL OBS TONAN TACUB
Keywords: MAGNETIC, FIELD REVERSAL, COROLLARY, MECHANISM, ORIGIN, SPIRAL STRUCTURE; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS